Pemanfaatan Teknologi IoT Untuk Monitoring Suhu Dan Kelembaban Gudang Pangan - Fathurrohman; Edi Wahyudin; Muhammad Zamil Farhan; Nazwa Putri Nindya (CV. Multi Kreasi Media, 2023)
The storage of food products in warehouses requires strict monitoring of environmental conditions, particularly temperature and humidity, to maintain the quality and shelf life of the products. Unstable temperature and humidity levels can trigger the growth of microorganisms, accelerate spoilage, and reduce the market value of the commodities. In this context, the Internet of Things (IoT) technology emerges as a strategic solution that enables real-time monitoring systems to operate automatically and efficiently. This Student Creativity Program (Program Kreativitas Mahasiswa/PKM) aims to design and implement an IoT-based monitoring system to control temperature and humidity in food storage warehouses. The system utilizes a DHT22 sensor to measure temperature and humidity, an ESP32 microcontroller as the control center, and a web-based or mobile application interface platform connected online to monitor the warehouse environment in real time. The collected data is periodically transmitted to a server and can be accessed by users through a dashboard equipped with notification features to alert when conditions exceed predefined thresholds. The methods employed in this project include system design, hardware and software integration, system testing in a food warehouse environment, and performance evaluation. The implementation results indicate that the IoT system can monitor temperature and humidity accurately and in real time. The system also successfully provides early warnings regarding unfavorable environmental conditions, allowing business operators to take immediate corrective actions. The application of this technology not only improves operational efficiency in food warehouse management but also serves as a form of technological education for local industry players, particularly MSMEs (Micro, Small, and Medium Enterprises) in the agribusiness sector. It is expected that this system model can be widely adapted across various food storage sectors to prevent losses due to improper storage conditions.